2012
DOI: 10.5194/tc-6-287-2012
|View full text |Cite
|
Sign up to set email alerts
|

Use of a thermal imager for snow pit temperatures

Abstract: Abstract. Weak snow of interest to avalanche forecasting often forms and changes as thin layers. Thermometers, the current field technology for measuring the temperature gradients across such layers -and for thus estimating the expected vapour flux and future type of crystal metamorphism -are difficult to use at distances shorter than 1 cm. In contrast, a thermal imager can provide thousands of simultaneous temperature measurements across small distances with better accuracy. However, a thermal imager only sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
1
23
1
Order By: Relevance
“…As well, if thermal conductivity properties play a role, this will add more uncertainty in the interpretation of the thermal signal. Shea et al (2012c) found no relevant sharpening of gradients with exposure time. This finding is opposite to what is presented here.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…As well, if thermal conductivity properties play a role, this will add more uncertainty in the interpretation of the thermal signal. Shea et al (2012c) found no relevant sharpening of gradients with exposure time. This finding is opposite to what is presented here.…”
Section: Discussionmentioning
confidence: 91%
“…Crusts showed the same surface energy balance process as artificial concavities. However, this does not prove that internal processes in an undisturbed snowpack are not existent to explain a warm crust, as done by Shea et al (2012c). The initial warm crust shown in Figs.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations